CD147 regulates the Rap1 signaling pathway to promote proliferation, migration, and invasion, and inhibit apoptosis in colorectal cancer cells - Fu Xiaoxia; Li Rui; Chen Meiru; Yuan Lu; Jin Ying (Scientific Reports)
Abstract The malignant progression of colorectal cancer (CRC) is intimately associated with the abnormal regulation of transmembrane glycoprotein CD147. However, the molecular mechanism via the Rap1/Rap1GAP signaling axis has not been elucidated. This study, through integrated bioinformatics analysis, discovered that the expression of CD147 in CRC tissues was significantly higher than that in adjacent tissues, and patients with high expression had a shorter overall survival. Immunohistochemistry and Western blot confirmed that the expression level of CD147 protein in CRC tissues was higher than that in adjacent tissues. Moreover, qRT-PCR verified a positive correlation between the expressions of CD147 and Rap1. Immunofluorescence clearly indicated that CD147 was specifically enriched in the cell membrane and cytoplasm of SW620 cells. The knockdown of CD147 mediated by shRNA could inhibit the proliferation of HCT116/SW620 cells, induce apoptosis, and weaken the migration and invasion capabilities. The mechanism involved the downregulation of c-Myc, Bcl-2 and the upregulation of Bax, E-cadherin. The mechanistic study found that the knockdown of CD147 increased the expression of Rap1GAP and inhibited Rap1 activity. Overexpression of Rap1 could reverse the inhibitory effects of CD147 knockdown on proliferation, apoptosis, and EMT phenotypes. This study revealed that CD147 upregulated Rap1 expression while inhibiting Rap1GAP, thereby maintaining Rap1 activity and driving the malignant progression of CRC through the c-Myc/Bcl-2/Bax axis and EMT program, providing experimental evidence for precise treatment targeting the CD147-Rap1 signaling axis.